(untitled) (Eureka Journal of Humanities and Social Research, 2026)
The main objective of this article is to conduct an in-depth analysis of phraseological units in the English language. In the course of this study, the meanings, cultural significance, etymology, and structural characteristics of these phraseological units are examined in detail.